Endothelin 1 gene is not a major modifier of chronic kidney disease advancement among the autosomal dominant polycystic kidney disease patients - Annapareddy Shiva Nagendra Reddy; Elumalai Ramprasad; Lakkakula Bhaskar V.K.S; Ramanathan Gnanasambandan; Periyasamy Soundararajan (Society of Diabetic Nephropathy Prevention, 2016)
Introduction: Autosomal dominant polycystic kidney disease (ADPKD) is characterized by the presence of numerous cysts in the kidney and manifest with various renal and extra-renal complications leading to ESRD. Endothelin may contribute to various renal and extra-renal manifestations pointing to genetic and environmental modifying factors that alter the risk of developing chronic kidney disease (CKD) in ADPKD. In the present study we investigated six genes coding for endothelin 1 (EDN1) tagging-single nucleotide polymorphisms (tag-SNPs) to unravel the EDN1 gene modifier effect for renal disease progression in ADPKD. Materials and Methods: The tag-SNPs were genotyped using FRET-based KASPar method in 108 ADPKD patients and 119 healthy subjects. Cochran-Armitage trend test was used to determine the association between ADPKD and EDN1 tag-SNPs. Multivariate logistic regression analysis was performed to assess the effect of tag-SNPs on CKD progression. The relationship between different CKD stages and hypertension and their interaction Mantel-Haenszel stratified analysis was performed. Results: All loci are polymorphic and followed Hardy-Weinberg equilibrium. Distribution of EDN1 genotypes and haplotypes in control and ADPKD is not statistically significant. Five SNPs covering 3.4 kb forming single LD block, but the LD was not strong between SNPs. The EDN1 genotypes are not contributing to the CKD advancement among the ADPKD patients. Conclusion: These results suggest that the EDN1 gene is not a major modifier of CKD advancement among ADPKD patients.